The Implicit Meaning and Its Reflection in The Field of Pragmatic: The Short Story (Niziki Domahiya) As A Model. - Ali, Sherzad; Masiha, Rjeyan (Humanities Journal of University of Zakho, 2021)
implicit meaning is a type of meaning, and in general it has a role in the field of pragmatics. This research, which titled (The implicit meaning and its reflection in the field of pragmatics, the short story "Niziki Domahiya" by Sabih Muhammad Hassan as a model), it attempts to address the implicit meaning and its reflection in the areas of pragmatics within this story, as the pragmatics in that story reflects the meaning and clarifies it through the context. The study used the descriptive analytical method by relying on the statistical method. The main objective of this study is to show the percentage of each pragmatic field with its types and sections that carry the implicit meaning. The research consists of an introduction and two chapters, as well as a conclusion, which includes the most important findings of the study. The first chapter deals with the implicit meaning, its concept and dimensions, while the second chapter is devoted to the applied field that represents the implicit meaning and the pragmatic fields, and discusses the reflection of the implicit meaning within these fields, by applying it to the story (Neezeki Dumahiya).